Through the eyes of the implementers: Practical guidelines to support community projects through monitoring and evaluation in rural areas - DIPELA, PERCY (Universitas Nahdlatul Ulama Surabaya, 2025)
One of the challenges facing many governments today, including the South African government, is eradicating poverty and putting Monitoring and Evaluation (M&E) systems in place to support poverty alleviation initiatives. Many poverty alleviation projects under social workers' supervision seem unsustainable even though M&E is performed continuously. This study aims to gain an in-depth understanding of mechanisms applied by social workers to support poverty alleviation projects and to propose the criteria and guidelines for consideration when supporting these projects. This study employed the phenomenological research design with descriptive, exploratory, and contextual research constructs. Purposive sampling was used to select participants, and data was collected using a semi-structured interview guide with open-ended questions in face-to-face interviews. Ethical considerations such as confidentiality, anonymity, and informed consent were followed. This study established a need for participant training on M&E to improve sustainability and accountability. Also, there are no clear standards to guide M&E activities. There is a need for a robust M&E system that should be able to answer the evaluation questions, promote learning, and satisfy accountability needs without being rigidly inflexible. The paper concluded that a lack of structured M&E activities and functioning impact results in poor implementation. Therefore, paying attention to when, how, and who should be involved in monitoring and evaluation will be necessary. The study proffered guidelines for consideration by social service professionals and practice-based initiatives to improve M&E activities initiatives to support projects.